The viral Ki-ras gene must be expressed in the G2 phase if ts Kirsten sarcoma virus-infected NRK cells are to proliferate in serum-free medium. - Durkin, J P (1987)
NRK cells infected with a temperature-sensitive Kirsten sarcoma virus (ts371 KSV) are transformed at 36 degrees C, but are untransformed at 41 degrees C which inactivates the abnormally thermolabile oncogenic p21Ki product of the viral Ki-ras gene. At 41 degrees C, tsKSV-infected NRK cells were arrested in G0/G1 when incubated in serum-free medium, but could then be stimulated to transit G1, replicate DNA, and divide by adding serum at 41 degrees C or dropping the temperature to a p21-activating 36 degrees C without adding serum. When quiescent cells at 41 degrees C were stimulated to transit G1 in serum-free medium by activating p21 at 36 degrees C and then shifted back to the p21-inactivating 41 degrees C in the mid-S phase, they continued replicating DNA but could not transit G2. Reactivating p21 in the G2-arrested cells by once again lowering the temperature to 36 degrees C stimulated a rapid entry into mitosis. By contrast, while serum-stimulated quiescent G0 cells at 41 degrees C replicate DNA and divide, serum did not induce G2-arrested cells to enter mitosis, indicating that serum growth factors may trigger events in the G1 phase that ultimately determine G2 transit. These observations made with the viral ras product suggest that cellular ras proto-oncogene products have a role in G2 transit of normal cells.